Exploring the DNA intercalating potential of glycosylated tetrathiafulvene (TTF) and dithiolene derivatives - Janairo, Jose Isagani B. (Animo Repository, 2011)
The DNA intercalating potential of the previously prepared water-soluble glycosylated tetrathiafulvene (TTF) and dithiolene derivatives was assessed through comparative docking analysis using doxorubicin as the reference molecule. Comparing the binding orientations and statistical evaluation of the ten lowest energy poses of each molecule with doxorubicin revealed that the glycosylated TTF derivatives are more likely to possess DNA intercalating activity since they posses lower energy values although adopted a different binding orientation. Results obtained will provide important preliminary insight on the possible biological applications of these glycoconjugates and may aid further development of these compounds for the intention of utilizing them as anti-tumor agents. © 2011 Analele Universitǎţii din Bucuresti.